IMPRESSION MANAGEMENT STRATEGY OF JOKOWI ON INSTAGRAM DURING INDONESIA'S PRESIDENTIAL ELECTION CAMPAIGN IN 2019 - Rosadi, Raesita Rakhmawati; Wiradharma, Gunawan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
Media plays an essential tool for every candidate to construct and promote their positive images in every election. In the vast development of the Internet and digital media, it is not enough for presidential candidates to only use mainstream media such as television, radio, and printed media. That’s why every presidential candidate must use the Internet, especially social media, to gain purposes. In the 2019 Indonesia Presidential Election, Instagram becomes popular for candidates to promote their self-image. This study will analyze Joko Widodo's personal Instagram account @jokowi three months before election. This study shows that Joko Widodo uses Instagram as his front stage to build his positive image by using several issues such as; his success in building infrastructure, maintaining commodity prices in the market, his concern towards Indonesian athlete achievements, and his fast reaction to natural disasters events. He creates positive image by showing his other side as husband and grandfather. Moreover, he uses his closeness with people to deliver that he is a caring leader. This study suggests that public be more critical in reading message of political campaigns in presidential candidates. It only provides positive issue identified as a front stage that hides the actual reality